Analysis Bibliometric: Character Education Research in Elementary Schools on One Decades - Bella Yolandini; Cik Suabuana; Ilham Muhammad; Fadli Agus Triansyah (STKIP Yapis Dompu, 2023)
Character education is an educational process that seeks to shape a person's personality or character in order to instill them with moral ideals, ethics, and positive attitudes. Character education focuses not just on academics, but also on the development of personality traits such as attitudes, values, morality, empathy, cooperation, and creativity. Objective study This that is to find out trends and identify publications related to character education in elementary schools, and visualize them. The research method used is a bibliometric method or analysis related to character education in elementary schools. The analysis used is evaluative and descriptive bibliographic analysis. The subjects in this study were 164 publications collected from the database dimensions according to the specified keywords . The results of the study show that the number of publications related to character education in elementary schools in Indonesia has increased in recent years, starting from 2017 to 2021. The highest number of documents is at the institution or university